2015
DOI: 10.1111/iej.12452
|View full text |Cite
|
Sign up to set email alerts
|

The influence of two reciprocating single‐file and two rotary‐file systems on the apical extrusion of debris and its biological relationship with symptomatic apical periodontitis. A systematic review and meta‐analysis

Abstract: This systematic review and meta-analysis investigated the influence of the number of files (full-sequence rotary-file versus reciprocating single-file systems) used during root canal preparation on the apical extrusion of debris and its biological relationship with the occurrence of symptomatic apical periodontitis. An extensive literature research was carried out in the Medline, ISI Web of Science and Cochrane databases, for relevant articles with the keyword search strategy. Based on inclusion and exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
129
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 58 publications
(221 reference statements)
4
129
1
13
Order By: Relevance
“…A systematic review and meta-analysis conducted by Caviedes-Bucheli[8] concluded that inflammatory reaction due to apical extrusion of debris is not influenced by the number of files but the type of movement and the instrument design. Therefore, this meta-analysis aims at comparing four different endodontic instrumentation systems showing varied type of movements (manual, rotary, reciprocation, and transline in-and-out vibratory motion).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis conducted by Caviedes-Bucheli[8] concluded that inflammatory reaction due to apical extrusion of debris is not influenced by the number of files but the type of movement and the instrument design. Therefore, this meta-analysis aims at comparing four different endodontic instrumentation systems showing varied type of movements (manual, rotary, reciprocation, and transline in-and-out vibratory motion).…”
Section: Discussionmentioning
confidence: 99%
“…, Caviedes‐Bucheli et al . ) and showed were associated with good cleaning efficiency in terms of debris and smear layer removal (Dagna et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was demonstrated that different root canal preparation techniques lead to the expression of different levels of inflammatory neuropeptides in the periapical periodontal ligament linked with the possible emergence of symptomatic apical periodontitis (Caviedes-Bucheli et al, 2013). It is believed that this is connected to the different amounts of extruded debris beyond the apical foramen (Caviedes-Bucheli et al, 2016). Since nearly all root canal instrumentation techniques including hand instrumentation as well as engine driven instruments lead to apical extrusion of debris (Al-Omari & Dummer, 1995; Bürklein & Schäfer, 2012; Capar et al, 2014; De-Deus et al, 2010) in most cases there will be an inflammatory response to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…In an in-vitro study reciprocating instruments extruded more debris than rotary instruments (Bürklein & Schäfer, 2012) with Reciproc producing most debris while another in-vitro study found Reciproc to produce significantly less extruded debris compared to rotary techniques (Kocak et al, 2013). The only clinical studies measuring the expression of inflammatory neuropeptides in the periodontal ligament found that the instrument design of engine driven root canal instruments has a greater impact on expression of neuropeptides than the instrumentation technique (Caviedes-Bucheli et al, 2016). Because of this contradictory data situation and the limited knowledge, if the amount of expressed neuropeptides can be directly correlated to the perceived pain it remains unclear if there is an impact on the postoperative pain levels of patients after root canal treatment.…”
Section: Discussionmentioning
confidence: 99%